Performance, metabolism and nitrogen use efficiency in dairy cows fed low protein, legume silage-based diets: a systematic review and meta-analysis - M.R. Chowdhury; R.G. Wilkinson; L.A. Sinclair (Animal)
The primary focus of low CP diets and the inclusion of legume silages for dairy cows is to decrease feed costs and mitigate the environmental impact of milk production. This systematic review and meta-analysis were conducted to evaluate the effects of dietary CP level on the performance, metabolism, and N use efficiency (NUE; g milk N output/kg N intake) of dairy cows fed legume-based rations. A total of 36 production trials with 102 treatment means were included, and the effect of dietary CP level was estimated using the raw-mean difference between control (high CP) and low CP diets. Publication bias was examined using Begg’s and Egger’s tests. Meta-regression and subgroup analyses were performed to explore the heterogeneity of the response variables. Reducing dietary CP from 171 g/kg DM to 145 g/kg DM in forage legume-based diets resulted in decreased DM intake (−0.62 kg/d), milk yield (−1.41 kg/d), milk protein (−0.22 g/kg), milk urea N (MUN; −3.47 mg/dL), plasma urea N (−1.85 mmol/L) and condition score (−0.03) in dairy cows. Similarly, nutrient intake, diet digestibility, total urine output, N excretion through milk, urine and faeces, urine N/total N intake, rumen ammonia-N and molar proportion of butyrate were decreased (P < 0.05) in cows receiving low CP diets compared with those fed the control. In contrast, low CP diets increased (P < 0.05) the faecal N/total N intake, NUE, and plasma content of non-esterified fatty acids. Subgroup analyses revealed that the effect size of DM intake, milk yield, MUN, urinary N excretion and rumen ammonia-N content had less of a negative impact (P < 0.05) when cows received dietary CP levels of 140–155 g/kg DM than < 140 g/kg DM. The inclusion of rumen-protected methionine in low CP diets increased (P = 0.04) DM intake and tended to improve (P = 0.08) the milk protein content of dairy cows. Feeding lucerne silage-based low CP diets showed an improvement (P < 0.05) in apparent diet digestibility but reduced milk yield (−1.46 kg/d) relative to red clover silage-based rations. The inclusion rate of legume silages in low-CP diets beyond 40% of the forage DM reduced (P < 0.01) DM intake and milk protein content. We conclude that legume silage-based low CP diets enhance NUE but have adverse effects on dairy cow performance that can partially be mitigated by including rumen-protected methionine and limiting their proportion in the forage component of the diet.